The Deterministic Behavior of Self-Incompatibility Alleles - Nagylaki, Thomas (1975)
For a system of n self-incompatibility alleles, neglecting mutation and random drift, it is shown that the completely symmetric equilibrium is locally stable, and any allelic frequency less than q = 1+a-(see PDF), where a = [2(n - 1)](-1), will increase. For all n, q > (2n)(-1), but if n > > 1, q ≈ (2n)(-1).